Reflective Goal Setting An Applied Approach to Personal and Leadership Development - Travers, Cheryl J. (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2022)
This book presents, for the first time, a comprehensive overview of the Reflective Goal Setting model, its theoretical framework and origins, and its practical applications for personal development, improved coping and reduced stress, academic growth and performance and leadership. Divided into three parts, the author begins by examining the particular importance of personal development, and in particular soft and interpersonal skills development. It addresses the limitations of current personal development and leadership education and training for the transfer of learning, before outlining how Reflective Goal Setting fulfils this need. It presents a critical review of Goal Setting Theory and approaches to reflective practice that demonstrates how the Reflective Goal Setting model was developed from, and builds upon, these earlier approaches. Drawing on original research and illustrative case studies, the author details the cyclical five step process of the Reflective Goal Setting model across 5 chapters - forming Part 2 of the book. Part 3 examines the practical applications and impact of using Reflective Goal Setting, employing illustrative case studies from a variety of settings including higher education, professional development and executive education. This innovative work will provide a valuable resource for researchers and practitioners in Organisational and Industrial Psychology, Education, and Business and Management and indeed anyone who wants to work on their own personal development. Cheryl J. Travers is Senior Lecturer in the Work and Organisation research group within the School of Business and Economics, Loughborough University, UK. Her research interests and publications include occupational stress, management of change, diary methods and the development of her Reflective Goal Setting model for personal development and the transfer of learning. She has extensive experience with corporate clients, as well as university students, and has designed and delivered management, leadership and team development programmes for the public and private sector, in addition to delivering numerous keynote lectures and two TEDx talks.
Part 1. The Development of Reflective Goal Setting -- 1. Introduction to Reflective Goal setting -- 2. Reflective Goal Setting and the Transfer of Learning -- 3. Reflective Goal Setting, Goal Setting Theory, and the Importance of Writing About Goals -- 4. The Nature and Importance of Reflection and Keeping a Reflective Diary -- Part 2. The Reflective Goal Setting Model -- 5. Stage 1: Enhancing Self-Awareness -- 6. Stage 2: Selecting Suitable Goals -- 7. Stage 3: Visualising Successful Goal Behaviours -- 8. Stage 4: Formulating a Goal Statement -- 9. Stage 5: Putting Goals into Practice -- Part 3. Practical Applications of Reflective Goal Setting -- 10. Reflective Goal Setting for Managing Stress and Enhancing Coping -- 11. Reflective Goal Setting and Its Impact on Academic Growth and Performance -- 12. Reflective Goal Setting for Leader Personal Development -- 13. Conclusions.
Keywords: Psychology, Industrial; Maturation (Psychology).; Management; Personnel management; Work and Organizational Psychology; Personal Development; Management; Human Resource Management